Adaptive pathfinding and utility AI implementation for a tower defense game - Andre, Terence (Nanyang Technological University, 2022)
The purpose of this project is to develop a game in the tower defense genre, along with an AI that can challenge the player and provide more replayability value to the game. A* algorithm was chosen as the core technique used to develop an adaptive pathfinding system that makes the AI appear smarter by adapting to the player’s actions. This adaptive pathfinding aims to make the player required to think and optimize their actions during gameplay. Aside from pathfinding, an AI system for enemy spawning was also developed. This enemy spawning AI uses a Utility-based system as the core technology to provide variability between replays and challenge the player by countering the player’s actions. This report covers the game design, game mechanics implementation, and AI system implementation using the Unity game engine.